Area Sampling on Aerial Photographs - Tiwari, K. P. (Indian Forester, 1974)
Information on area of various forest type is usually the most wanted information for forest inventories and management planning. Besides showing the spatial distribution of forest types, aerial photographs are very useful in getting area information quickly and cheaply by plot or transect sampling devices. Delineation of various forest types based on floristic composition of top canopy and management practices was carried out in West Dehra Dun Division inside the effective area of each photograph after preparing photo interpretation key based on one day's reconnaissance. Four strata were recognised namely Plain Sal, Hill Sal, Miscellaneous and Non-forest including blanks and river beds. Assuming a precision of ±5% (¯S×j=±5%) for the smallest of the major stratum (Hill Sal forest type) the proportion of various forest types was obtained through dot grid sampling using .5 cm spaced dot grid. Area proportions so obtained were adjusted, for misinterpretation and scale variation after 1% ground check. The adjusted proportions, adjusted area and their errors were worked out. Forest type map on 1-15840 scale was obtained.